Chronic exposure to excess iron promotes EMT and cancer via p53 loss in pancreatic cancer - Yangzom D. Bhutia; Jiro Ogura; Paul J. Grippo; Carolina Torres; Toshihiro Sato; Mitchell Wachtel; Sabarish Ramachandran; Ellappan Babu; Sathish Sivaprakasam; Devaraja Rajasekaran; Bradley Schniers; Nhu On; et al. (Elsevier, 2020)
Based on the evidence that hemochromatosis, an iron-overload disease, drives hepatocellular carcinoma, we hypothesized that chronic exposure to excess iron, either due to genetic or environmental causes, predisposes an individual to cancer. Using pancreatic cancer as our primary focus, we employed cell culture studies to interrogate the connection between excess iron and cancer, and combined in vitro and in vivo studies to explore the connection further. Ferric ammonium citrate was used as an exogenous iron source. Chronic exposure to excess iron induced epithelial-mesenchymal transition (EMT) in normal and cancer cell lines, loss of p53, and suppression of p53 transcriptional activity evidenced from decreased expression of p53 target genes (p21, cyclin D1, Bax, SLC7A11). To further extrapolate our cell culture data, we generated EL-KrasG12D (EL-Kras) mouse (pancreatic neoplastic mouse model) expressing Hfe+/+and Hfe−/− genetic background. p53 target gene expression decreased in EL-Kras/Hfe−/− mouse pancreas compared to EL-Kras/Hfe+/+ mouse pancreas. Interestingly, the incidence of acinar-to-ductal metaplasia and cystic pancreatic neoplasms (CPN) decreased in EL-Kras/Hfe−/− mice, but the CPNs that did develop were larger in these mice than in EL-Kras/Hfe+/+ mice. In conclusion, these in vitro and in vivo studies support a potential role for chronic exposure to excess iron as a promoter of more aggressive disease via p53 loss and SLC7A11 upregulation within pancreatic epithelial cells. Keywords: SLC7A11, p53, Iron, Heme, Epithelial-mesenchymal transition